Pengaruh Brand Image dan Harga Terhadap Keputusan Pembelian Mobil Toyota Avanza pada PT. Hasjrat Abadi Tendean Manado - Tirtaatmaja, Dais Iis; Tampi, Johny R. E.; Punuindoong, Aneke Y. (Sam Ratulangi University, 2019)
This research aims to determine the influence of Brand Image and Price on consumers purchasing decisions in PT. Hasjrat Abadi Tendean Manado. The population that used is all of the consumers’ of PT. Hasjrat Abadi Tendean Manado where the population size is unknown. The sample which is taken in this research is 96 respondents who had used Toyota Avanza and used the simple random sampling technique. The sample based on respondent level techniques and the data collection method with using questionnaire. The statistical analysis that used in this research in linear regression analysis with using SPSS 25 for windows. The result of this research demonstrate that the Brand Image and Price have a positive influence and have significant influence on purchasing decisions. The amounts of Brand Image and Price influence on purchasing decisions are 59,5% and 40,5% which are influenced by other variables. Based on the results of multiple linear regression analysis that the brand image and price variables have a significant and positive effect on purchasing decisions.